I WAS BORN FREE, AND TO BE ABLE TO LIVE FREE, I CHOSEN... - Pachas Serrano, Miguel (2020)
This paper seeks to determine whether the Constitution recognizes women’s reproductive freedom or autonomy which in turn includes the freedom to terminate the pregnancy. We believe that from freedom, equality and non-discrimination constitutional as well as the dignity of the human person is possible to argue that freedom is recognized by the Constitution.Constitution – constitutional liberty - equality and non-discrimination constitutional - Dignity of the human person – autonomy – equality and positive valuation differences – prenatal life – conceived – abortion